Paradiplomasi Melalui Kerjasama Sister City: Sebuah Upaya Untuk Meningkatkan Potensi Industri Pariwisata di Kabupaten Sumenep - Alia Rizka Mansyur (PUBLIC CORNER, 2021)
This study aims to increase the potential for tourism in Sumenep district by using the concept of sister city collaboration paradiplomacy as one of the local government innovation efforts in providing welfare and the community's economy. In line with the globalization process, international relations actors also extend not only to state actors but also to non-state actors such as international organizations, NGOs, MNCs, media, regions, minority groups. , even individuals. From this we can see that the various actors involved in foreign relations and cooperation are increasingly complex, especially in the decision-making process. The research method, the researcher used the literature study method. Literature study, namely the researcher diligently examines the literature needed in the study. The many potentials of the tourism industry in Sumenep regency are not yet optimal, the efforts of the Sumenep district government to use sister city cooperation are one of the solutions to increase local and foreign tourists. Keywords: Paradiplomacy, Sister City, Tourism, Sumenep